Participation in Socialization, Work Profession, Knowledge of Fire Safety Simulation Capabilities According to MFK 7 Snars Accreditation Standards at Bhayangkara Hospital Nganjuk - Hari, Prasetyo Umar; Indasah, Indasah (Journal for Quality in Public Health, 2021)
Background: The high number of hospital fire cases demands that all hospitals be able to carry out fire safety. The ability to fire safety must be able to be carried out by all hospital officers, both health and non-health workers (all work professions). The research objective was to analyze the factors that influence the simulation ability of fire safety management according to the MFK 7 SNARS accreditation standard at Bhayangkara Hospital Nganjuk. Subjects and methods: Explanatory survey research design using a cross-sectional approach. The research was conducted from January 16 to February 18, 2021 with a sample of 170 people. Independent variables are participation in socialization, work profession, and knowledge of fire safety. The dependent variable is the ability to simulate fire safety according to the MFK 7 SNARS accreditation standard. The data collection tools used a questionnaire. Data analysis used multiple logistic regression. Results: Participation in socialization (OR = 2.36; 95% CI = 1.04-5.33; p <0.039), knowledge of fire safety (OR = 3.18; 95% CI = 1.45-6.93; p <0.004), significantly increased the ability to simulate fire safety according to MFK 7 SNARS accreditation standards. Work profession (OR = 1.03; 95% CI = 0.54-1.96; p <0.934) does not affect the ability of fire safety management simulation according to MFK 7 SNARS accreditation standards which is statistically significant. Conclusion: Participation in socialization and knowledge about fire safety increases the ability to simulate fire safety according to MFK 7 SNARS Accreditation standards.